CHALLENGES IN TEACHING READING - Salakhova , Elza Zagirovna (Innovative Development in Educational Activities, 2022)
It is in consideration to this that the aim of this investigation is to identify the problems of teaching reading in a non native speaking classroom and the way in which these skills are developed for students of English as a foreign language. The author analyses the problem considering the issues of developing students’ reading skills and the challenges that the learners encounter in reading process. The aim of this article is not only considering the problem above-mentioned but to give some recommendations concerning the issue as well.